Production and Decomposition of Leaf Litter in Sal, Teak, Eucalyptus and Poplar Forests in Uttar Pradesh - Singh, Omkar; Sharma, D.C.; Rawat, J.K. (Indian Forester, 1993)
Annual leaf litter fall was estimated in natural Sal, plantations of Teak, Eucalyptus and Poplar as 6.86, 7.70, 6.51 and 5.29 oven dry t/ha respectively. The rate of decomposition per year in the four stands was highest in Sal (2.01), followed by Teak (1.26), Poplar (1.05) and least in Eucalyptus (0.69). These rates were found slightly higher than those worked out on the basis of forest floor accumulations. Time required to reach various levels of steady state accumulation or that of decay has also been calculated for the species. The mineralisation of various nutrients in the four stands has also been discussed.